RISIKO DEFISIENSI MINERAL DAN VITAMIN TERHADAP KEJADIAN STUNTING BALITA - Rr. Dewi Ngaisyah; Firlia Ayu Arini (Media Gizi Mikro Indonesia, 2023)
ABSTRACT Food directly influences the risk of stunting. Based on the nutritional status monitoring, there were found children with high prevalance of stunting and severe stunting in Public Health Center of Kalasan. The number fell on 20.71% in 2017. This study aimed to figure out the risk of mineral and vitamin deficiency in stunting children through Public Health Center of Kalasan. It was an observational study, conducting a case-control method. The study gathered 106 samples of children by the use of consecutive sampling technique. It collected the data by the help of z score index of weight-for-age. The data of food consumption were fetched via an interview using SQFFQ method. The data were analyzed using the bivariate test with Chi Square?? 0,05. The results of mineral and vitamin level in stunting children were as follows: zinc (p=0.011), iron (p=0.010), iodine (p=0.027), calcium (p=0.000), phosphorus (p=0.002), magnesium (p=0.001), vitamin A (p=0.05), vitamin D (p=0.004). There was a relationship between minerals and vitamins consumption to prevent stunting in children. This can inspire future studies to measure the food consumption, preferably using food weighing method for a more accurate results. ABSTRAK Kejadian stunting berkaitan secara langsung dengan konsumsi makanan. Hasil pemantauan status gizi memperlihatkan pravelensi balita stunting di Puskesmas Kalasan cukup tinggi, yaitu 20,71% pada tahun 2017. Penelitian ini bertujuan mengetahui risiko defisiensi mineral (Seng, Zat Besi, Yodium, Kalsium, Fosfor, Magnesium) dan vitamin (Vitamin A, Vitamin D) terhadap kejadian Stunting di wilayah kerja Puskesmas Kalasan. Penelitian ini merupakan penelitian observasional menggunakan rancangan case-control. Sampel penelitian sebanyak 106 balita dipilih menggunakan teknik consecutive sampling. Pengumpulan data stunting diperoleh dari perhitungan z score indeks TB/U, sedangkan data konsumsi diperoleh melalui wawancara menggunakan SQFFQ. Uji bivariat menggunakan Uji Chi Square?? 0,05. Berdasarkan penelitian yang dilakukan diketahui bahwa hasil bivariat sebagaimana terkait dengan kejadian stunting menunjukkan hasil yaitu seng (p=0,011), zat besi (p=0, 010), yodium (p=0,027), kalsium (p=0,000), fosfor (p=0,002), magnesium (p=0,001), vitamin A (p=0,05), vitamin D (p=0,004). Kesimpulan yang diperoleh dari penelitian yang dilakukan yaitu terdapat hubungan konsumsi mineral dan vitamin dengan kejadian stunting pada balita.